1983
DOI: 10.1093/ajcn/37.6.924
|View full text |Cite
|
Sign up to set email alerts
|

Further studies of the effect of a high protein diet as meat on calcium metabolism

Abstract: Previous studies in this Unit have shown that a high protein intake, given as meat, did not induce hypercalciuria, except for the initial and temporary increase in two subjects. In the present investigation the long-term effect of a high meat diet on calcium metabolism was studied for 78 to 132 days in four adult males and the short-term effect for 18 to 30 days in three subjects. Calcium and phosphorus balances and calcium absorption studies, using 47Ca as the tracer, were carried out. During the long-term hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 19 publications
4
19
0
2
Order By: Relevance
“…Under comparable experimental conditions, some intervention studies found that a HP diet (1.5-2 g/kg compared with 0.5-1 g/kg proteins consumed each day) induced an increase in calcium absorption associated with an increased calcium excretion in premenopausal and postmenopausal women (Kerstetter et al, 1998(Kerstetter et al, , 2005Hunt et al, 2009), whereas other studies found no effect of HP intake on calcium absorption, despite an increased calcium excretion (Kerstetter et al, 2006;Ceglia et al, 2009). A longitudinal observational study and interventions studies, using the radiotracer method to assess calcium balance, also did not find any effect of a HP diet on calcium intestinal absorption; but in these studies, no effect of the dietary protein was found on calcium excretion (Spencer et al, 1983;Dawson-Hughes and Harris, 2002;Roughead et al, 2003). The level of dietary calcium might modulate the effect of protein intake on calcium absorption and contribute to explain the conflicting results.…”
Section: Modulations Of Intestinal Dietary Calcium Absorptionmentioning
confidence: 82%
See 2 more Smart Citations
“…Under comparable experimental conditions, some intervention studies found that a HP diet (1.5-2 g/kg compared with 0.5-1 g/kg proteins consumed each day) induced an increase in calcium absorption associated with an increased calcium excretion in premenopausal and postmenopausal women (Kerstetter et al, 1998(Kerstetter et al, , 2005Hunt et al, 2009), whereas other studies found no effect of HP intake on calcium absorption, despite an increased calcium excretion (Kerstetter et al, 2006;Ceglia et al, 2009). A longitudinal observational study and interventions studies, using the radiotracer method to assess calcium balance, also did not find any effect of a HP diet on calcium intestinal absorption; but in these studies, no effect of the dietary protein was found on calcium excretion (Spencer et al, 1983;Dawson-Hughes and Harris, 2002;Roughead et al, 2003). The level of dietary calcium might modulate the effect of protein intake on calcium absorption and contribute to explain the conflicting results.…”
Section: Modulations Of Intestinal Dietary Calcium Absorptionmentioning
confidence: 82%
“…Increased urinary calcium excretion was also observed in omnivorous than in vegetarian women (Ball and Maughan, 1997) or in subjects following an Atkins diet (Reddy et al, 2002). However, other studies reported no change in the level of urinary calcium with the consumption of high-meat diets compared with low-meat diets (Spencer et al, 1978(Spencer et al, , 1983(Spencer et al, , 1988. The hypercalciuric effect of HP diets certainly depends on the nature of the dietary protein, and food with HP contents, such as meat or dairy products, also contain components that limit urinary calcium excretion.…”
Section: Protein Intake Urinary Calcium and Acid Excretions And Calcmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the effects of fat and protein on calcium nutrition are still unclear. It is important to note that there are also published reports that did not find significant influences of fat and protein on calcium absorption and/or retention (39,40). Attention has been drawn to the effects of fat malabsorption on calcium balance (37,38).…”
Section: And Discussionmentioning
confidence: 99%
“…The liberation of alkali from bone requires osteoclast-mediated bone resorption, which could over a prolonged period of time reduce skeletal mass (3)(4)(5)(6). In support of this hypothesis, balance studies in the 1970s reported no change in intestinal calcium absorption as dietary protein increased (7)(8)(9)(10)(11)(12)(13). However, more recent studies using dual-stable calcium isotopes found that in the short term, dietary protein significantly affects intestinal calcium absorption (14,15).…”
Section: Introductionmentioning
confidence: 99%